A comparative legal study on internet pharmacy in Malaysia, United States and United Kingdom / Nurhairani Abdul Latif, Normawati Mohamed Noor and Wan Maria Wan Mahmood. - Abdul Latif, Nurhairani; Mohamed Noor, Normawati; Wan Mahmood, Wan Maria (2011)
The Internet pharmacy does give benefits to consumers but it must be outweighed with the available risks mostly posed by anonymous Internet pharmacy operators. This study examines the existing laws or regulations and guidelines in Malaysia relating to Internet pharmacy and identifying present laws and control of Internet pharmacy in the United States and United Kingdom to be adopted in Malaysia. The research is carried out using qualitative research method, library research on the primary sources of the laws and statutes in Malaysia, United Kingdom and United States as well as interviews conducted personally in Malaysia and through email for international agencies. The issues and challenges are divided into legal aspects, enforcement activities and socio-economic. There are quite a number of approaches that can be implemented by the authority in Malaysia in order to enhance the standard and quality of the Internet pharmacy. This include the amendment of the existing legislations to suit with the development of information technology, enhancing the training of the pharmacy enforcement officer, verification system of the internet pharmacy, creating specialized unit in handling those cases, and boosting the consumer education program. With the growth of E-commerce, the law must continue to growth and accommodate the new technology because the goal of regulation is to promote the health and safety of Internet users while not stifling the growth of the modern medium. Cooperation between state, professional organization and the federal government are also vital in order to address the issues associated with Internet pharmacy.